2019
DOI: 10.1371/journal.pone.0221400
|View full text |Cite|
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease is a risk factor for large-for-gestational-age birthweight

Abstract: Objective Nonalcoholic fatty liver disease (NAFLD) is a well-recognized hepatic manifestation of metabolic disease in adults and has been associated with the development of gestational diabetes (GDM). Hepatic insulin resistance can result in increased release of glucose (from gluconeogenesis) and free fatty acids (due to enhanced lipolysis), which can lead in turn to fetal overgrowth. However, the relationship between maternal metabolic factors (such as circulating levels of triglycerides, free fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 28 publications
(26 reference statements)
1
50
0
Order By: Relevance
“…There were 12 prospective cohort studies that reported a total of 17,731 cases, 4,430 of which included LGA newborns. Maternal lipid profiles were measured in the first trimester in four articles 3,9,14,15 ; in the second trimester Fasting TC, TG, HDL-C, LDL-C Table 3. Mean values of lipid profiles during pregnancy in women with LGA newborns and controls.…”
Section: Study Characteristics and Assessment Of Risk Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 12 prospective cohort studies that reported a total of 17,731 cases, 4,430 of which included LGA newborns. Maternal lipid profiles were measured in the first trimester in four articles 3,9,14,15 ; in the second trimester Fasting TC, TG, HDL-C, LDL-C Table 3. Mean values of lipid profiles during pregnancy in women with LGA newborns and controls.…”
Section: Study Characteristics and Assessment Of Risk Biasmentioning
confidence: 99%
“…Most of the studies 4,6,7,15 used the INTERGROWTH-21st definition of >90th percentile for LGA newborns. Some studies in China 3,19 used a referred percentile standard based on a Chinese population, and some 14,16,18 used their country's definition of LGA. A detailed list of the implemented eligibility criteria for each study is shown in Table 2, and the mean values of the determined biochemical lipids are presented in Table 3.…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations